Emotional intelligence, achievement goals, and academic performance: a study with undergraduate students of accounting sciences - Costa, Luisi Corvo (2022)
This study analyzed the relationship between Emotional Intelligence (EI), adherence to the Achievement Goals Theory (AGT), and academic performance of undergraduate’s students of Accounting Sciences from a Federal Higher Education Institution in Rio Grande do Sul. It was carried out through a survey by an electronic questionnaire, sent to the emails and social media of Accounting Science students enrolled in March of 2020, resulting in a sample with 99 completed surveys. The results demonstrate a significant relationship between EI and adherence to the AGT. However, in this study, in general, it was not possible to observe a significant statistical influence (p ≥ 0.05) that the level of EI and adherence to the AGT influence the average academic performance. The findings contribute to the previous literature on emotional intelligence, as well theoretical and practical contributions to teaching and the accounting profession. Regarding the practical contributions to teaching and the accounting profession, the assistance to teachers, coordinators and educational institutions is highlighted to observe that the environment outside the classroom influences the levels of emotional intelligence, objectives, and academic performance of the students, in addition to helping teachers understand which interaction method can be used in the teaching-learning process, according to the students' emotional intelligence level. Based on the systematic analysis of the literature, we believe this is the first work that aims to assess the relationship between academic performance, level of EI, and adherence to AGT in undergraduate Accounting Sciences students in Brazil, which gives the study an unprecedented character.